Association of CDH11 with non‐syndromic ASD. Issue 5 (19th May 2014) - Crepel, An; De Wolf, Veerle; Brison, Nathalie; Ceulemans, Berten; Walleghem, Didier; Peuteman, Gilian; Lambrechts, Diether; Steyaert, Jean; Noens, Ilse; Devriendt, Koen; Peeters, Hilde
<x xml:space="preserve">Abstract</x> We report a sporadic patient with Autism Spectrum Disorder (ASD), mild intellectual disability and attention deficit hyperactivity disorder (ADHD) with a de novo partial deletion of CADHERIN 11 (CDH11). The deletion is associated with one of the breakpoints of a de novo complex chromosomal rearrangement 46, XY, t(3;16;5)(q29;q22;q15)inv4(p14;q21)ins(4;5)(q21;q14.3q15). Cadherins are cell adhesion molecules involved in synaptic plasticity. Since genetic evidence points towards a role for cadherins in ASD, we studied the possible contribution of CDH11 to ASD. A case‐control association study for 14 SNP variants in 519 ASD cases and 1, 192 controls showed significant overrepresentation of rs7187376C/C genotypes in the patient group [P = 0.0049 (Chi‐square = 7.90 1 df) and O.R. 3.88 C.I. = 1.403–10.733]. There was no association for C/T versus T/T [P = 0.6772 (Chi‐square = 0.17 1 df)] nor was there association at the allelic level [P = 0.4373 (Chi‐square = 0.6 1 df)]. In addition to the association of common variants in CDH11 with ASD, we studied the possible contribution of rare variants by sequencing CDH11 in 247 patients, and found three novel variants in the coding region of CDH1, of which two variants were unlikely to be causal. Targeted CNV screening in these 247 patients did not reveal copy number variation in CDH11. In conclusion, the data provide evidence for the involvement of CDH11 in ASD which is consistent with the association of other cadherins with ASD and neuropsychiatric diseases. © 2014 Wiley Periodicals, Inc.